The Role of Fruit Juices and Nectars in the Prevention of Neurodegenerative Diseases - Guiné, Raquel (2017)
There are diverse conditions which affect the neurons in the human brain, and which are generically known as neurodegenerative diseases. The neurons are the structural blocks of the nervous system, this including both the brain and spinal cord. Unlike other cells in the human body, neurons normally don’t reproduce or substitute themselves, and hence, when they are damaged or die they cannot be replaced by the body. Some known examples of neurodegenerative diseases include amyotrophic lateral sclerosis, Parkinson’s, Alzheimer’s, and Huntington’s disease. Because the neurodegenerative diseases are incurable and debilitating conditions that result in progressive degeneration and/or death of nerve cells, they result in problems with movement (called ataxias), or mental functioning (called dementias). Because there is no effective cure for the neurodegenerative diseases, a great challenge lies in prevention, based on some identified risk factors. A balanced diet has proven to be beneficial for the human health in general, with fruits and vegetables as some of the healthier foods, with many documented positive outcomes for improvement of human condition. Fruits and fruit juices, being rich in many bioactive compounds with high bioavailability, can be major allies in the prevention of some neurodegenerative diseases. Hence, this chapter will focus on the role of fruit juices or fruits components in general on prevention of some of the most relevant neurodegenerative diseases.